2016
DOI: 10.1002/nbm.3600
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous multi‐slice (SMS) acquisition enhances the sensitivity of hemodynamic mapping using gas challenges

Abstract: Hemodynamic mapping using gas inhalation has received increasing interests in recent years. Cerebrovascular reactivity (CVR), which reflects the ability of the brain vasculature to dilate in response to a vasoactive stimulus, can be measured with CO2 inhalation while continuously acquiring BOLD MRI images. Cerebral blood volume (CBV) can be measured with O2 inhalation. These hemodynamic mapping methods are appealing because of their absence of gadolinium contrast agent, ability to assess both baseline perfusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
1
7
1
Order By: Relevance
“…It should also be noted that rs-CVR method has been directly validated with CO2based CVR in healthy controls [18]. The spatial correlation between rs-CVR and CO2-based CVR was 0.88 in healthy controls, which was similar to the intra-subject correlations of rs-CVR maps (0.91) [18] and CO2-based CVR maps (0.93) [40].…”
Section: Discussionsupporting
confidence: 67%
“…It should also be noted that rs-CVR method has been directly validated with CO2based CVR in healthy controls [18]. The spatial correlation between rs-CVR and CO2-based CVR was 0.88 in healthy controls, which was similar to the intra-subject correlations of rs-CVR maps (0.91) [18] and CO2-based CVR maps (0.93) [40].…”
Section: Discussionsupporting
confidence: 67%
“…Use of EPI with parallel imaging compared to spiral imaging, reduced signal loss due to susceptibility-induced magnetic field gradients in BOLD-CVR measurements without affecting sensitivity, which was defined as the CVR t-statistic (n = 5) (Winter et al, 2009). Furthermore, one study (n = 5) showed that using simultaneous multi-slice acceleration of factor 2 and 3, can reduce scan duration by at least a half compared to conventional EPI while maintaining the CVR sensitivity (Ravi et al, 2016a). Compared to single-echo ASL or BOLD EPI, a multi-echo (four echoes) EPI acquisition followed by T2 * fitting of the signal decay had higher inter-scan repeatability of breath-hold CVR analysed across voxels, CVR sensitivity and test-retest reliability analysed using the intra-class correlation coefficient (n = 14) (Cohen and Wang, 2019).…”
Section: Mri Techniquementioning
confidence: 99%
“…Finally, the increasing availability of simultaneous multislice and other parallel imaging techniques on commercial MR scanners will facilitate higher spatial and/or temporal resolution in future studies. 38 The ''HARNESS'' (Harmonising Brain Imaging Methods for Vascular Contributions to Neurodegeneration) collaboration, currently in progress, and ongoing discussions within the wider CVR community, should result in further recommendations and guidance relevant to the conduct of CVR experiments in SVD research.…”
Section: Discussionmentioning
confidence: 99%